DOUBLE-NUMBER MARKING MATTERS FOR BOTH L1 AND L2 PROCESSING OF NONLOCAL AGREEMENT SIMILARLY: AN ERP INVESTIGATION. Issue 5 (7th December 2022) - Cheng, Yesi; Cunnings, Ian; Miller, David; Rothman, Jason
Abstract: The present study uses event-related potentials (ERPs) to examine nonlocal agreement processing between native (L1) English speakers and Chinese–English second language (L2) learners, whose L1 lacks number agreement. We manipulated number marking with determiners ( the vs. that/these ) to see how determiner-specification influences both native and nonnative processing downstream for verbal number agreement. Behavioral and ERP results suggest both groups detected nonlocal agreement violations, indexed by a P600 effect. Moreover, the manipulation of determiner-number specification revealed a facilitation effect across the board in both grammaticality judgment and ERP responses for both groups: increased judgment accuracy and a larger P600 effect amplitude for sentences containing violations with demonstratives rather than bare determiners. Contrary to some claims regarding the potential for nonnative processing, the present data suggest that L1 and L2 speakers show similar ERP responses when processing agreement, even when the L1 lacks the relevant distinction.